Upaya Meningkatkan Hasil Belajar Matematika pada Materi Operasi Campuran Bilangan Bulat dengan Model Pembelajaran Kooperatif Tipe STAD (Student Team Achievement Divisions) Siswa Kelas IV SD Negeri Karyabakti IV - Chandra Sagul Haratua; Ujang Muhaemin; Dede Supriadi; Baban Maulana (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
This research was conducted at SD Negeri Karyabakti IV, aimed to determine whether the cooperative learning model of STAD (Student Teams Achievements Divisions) could enhance mathematics learning outcomes on the topic of mixed operations of integers for fourth-grade students at SD Negeri Karyabakti IV. The subjects of the study were 37 fourth-grade students consisting of 22 male students and 15 female students. Data collection was carried out through observations conducted by the school principal and peers, and also by assessing students' mathematics learning outcomes through written tests. The results of this study can be summarized as follows: 1) The Student Teams Achievement Divisions (STAD) learning method applied by the researcher to fourth-grade students at SD Negeri Karyabakti IV, focusing on the topic of mixed operations of integers, could enhance students' mathematics learning outcomes. This can be seen in the improvement of students' mathematics learning outcomes from the pre-cycle stage with a KKM completeness rate of 10.81%, which increased to 45.54% in the first cycle and further increased to 72.97% in the second cycle. 2) The mathematics learning using the Student Teams Achievement Divisions (STAD) method also improved teacher performance.